2015
DOI: 10.1093/tropej/fmv083
|View full text |Cite
|
Sign up to set email alerts
|

Severe Childhood Anaemia and Blood Transfusion in a Nigerian Secondary Level Facility

Abstract: This study aimed to describe the pattern and immediate outcome of severe childhood anaemia requiring blood transfusion at a secondary level of care in Nigeria. A cross-sectional survey of children hospitalized in a secondary health facility in Ogun State, Nigeria, with packed cell volume <20% and who received blood transfusion was done. Of the 253 children admitted between March 2013 and June 2014, 79 (31.2%) had severe anaemia and were transfused with blood. Two-thirds had multiple transfusions. Higher rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 20 publications
3
13
1
Order By: Relevance
“…Blood use among the other patient populations of pediatrics, obstetrics and gynecology, cesarean section births, and newborns are shown in Appendices S3.3 through S3.7. The studies among pediatric patients showed that 64% (2810 of 4387) of blood products were transfused for malaria. Postpartum hemorrhage (PPH) at 24% (524 of 2228) and cesarean sections at 22% (485 of 2228) were the most transfused diagnostic categories among the obstetrics and gynecology patients, with abortions and cancer accounting for only 10% and 8% of transfusions, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood use among the other patient populations of pediatrics, obstetrics and gynecology, cesarean section births, and newborns are shown in Appendices S3.3 through S3.7. The studies among pediatric patients showed that 64% (2810 of 4387) of blood products were transfused for malaria. Postpartum hemorrhage (PPH) at 24% (524 of 2228) and cesarean sections at 22% (485 of 2228) were the most transfused diagnostic categories among the obstetrics and gynecology patients, with abortions and cancer accounting for only 10% and 8% of transfusions, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These 10 studies were used for the primary outcome calculation. The rest of the studies evaluated blood use among specific patient groups: nine studies among pediatric patients only; five on obstetrics and gynecology patients; three among cesarean section deliveries; three among newborn babies; two among elective surgical operations; two exclusively on the use of platelets; two on the use of autologous blood; and one among hepatogastroenterology patients . Most studies made a clear distinction between the number of patients transfused and the number of blood products used for transfusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In developing countries of Africa malaria (95%), IDA (36.7%), and sickle cell anemia(31.7%) were the predominant causes indicating significant regional differences in the etiology of severe anemia. [26,27] China has lesser rates of anemia(24.4%) compared to India. [28] India has the highest IDA in comparison to rest of the world.…”
Section: Discussionmentioning
confidence: 99%
“…It is a common procedure in hospitalized children under the age of five years in malaria endemic countries because of their vulnerability to severe anaemia. [ 1 ] Other groups of children often transfused are those with hematological conditions, cancers and sick neonates. Sick neonates are intensively transfused due to common underlying conditions such as severe unconjugated hyper bilirubinaemia, neonatal sepsis, bleeding disorder, prematurity and anaemia from other causes.…”
Section: Introductionmentioning
confidence: 99%